2017
DOI: 10.1039/c6ta10517c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into the formation of porous carbons from gelatin

Abstract: Iron salts can change the structure and viscoelastic properties of the gelatin biopolymer and drive the formation of foams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The role of different salts on the initial foaming process has been investigated and was reported to affect the macro structure of the material. 45 This effect was observed here as the Co(NO 3 ) 2 containing gel expanded to a greater volume during freeze drying than the other cobalt salt containing gels. This does not appear to have any influence on the micro-structure since the surface area for the Co(NO 3 ) 2 based foam is smaller than the other samples although the low density fibrous material seen in SEM images may be influenced by the interaction between the salt and dextran chains.…”
Section: Materials Advances Papersupporting
confidence: 54%
See 1 more Smart Citation
“…The role of different salts on the initial foaming process has been investigated and was reported to affect the macro structure of the material. 45 This effect was observed here as the Co(NO 3 ) 2 containing gel expanded to a greater volume during freeze drying than the other cobalt salt containing gels. This does not appear to have any influence on the micro-structure since the surface area for the Co(NO 3 ) 2 based foam is smaller than the other samples although the low density fibrous material seen in SEM images may be influenced by the interaction between the salt and dextran chains.…”
Section: Materials Advances Papersupporting
confidence: 54%
“…Recently studies using gelatin with metal salts have found the interaction between the metals and the biopolymer in the initial foaming stage can have an impact on the macro porosity and structure of the final foam. 45 The metals exhibit a change in coordination environment when mixed with gelatin complicated by the pH and temperature of gel formation. The method of foam production is also reported to be important, slow heat drying produces collapsed pores whereas freeze drying the foams rapidly, produces high surface area materials.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, both diamond and graphite were included in our refinement (with correlations for r >5 Å removed) to model the mixture of sp 2 and sp 3 carbons that result from the decomposition of gelatin. 38 The C−C distances found in sp 2 and sp 3 carbons range from 1.4 to 1.5 Å, corresponding to the first peak in the PDF at ∼1.42 Å. As the majority of the scattering is produced by the Fe-containing phases and the primary purpose of this study is the structure of the Fe 3 N nanoparticles, we propose that this approximation for the carbon phase is sufficient.…”
Section: Resultsmentioning
confidence: 92%
“…This allows amorphous phases with a very short-range order to be approximated. Therefore, both diamond and graphite were included in our refinement (with correlations for r >5 Å removed) to model the mixture of sp 2 and sp 3 carbons that result from the decomposition of gelatin . The C–C distances found in sp 2 and sp 3 carbons range from 1.4 to 1.5 Å, corresponding to the first peak in the PDF at ∼1.42 Å.…”
Section: Resultsmentioning
confidence: 99%
“…The highly porous structure of a gelatin-derived framework also allows for metal ions to penetrate and dope the carbon structure, thereby further enhancing its efficiency as electrode material. Junke Ou et al developed hierarchical porous carbon materials (HPCMs) with nitrogen doping for sodium ion battery applications from the gelatin by potassium hydroxide (KOH) activation [ 28 , 29 , 30 , 31 ]. Inspired by this body of work, in this study, a novel 3D nitrogen self-doped graphene-based carbon aerogel is synthesized directly from gelatin (as a low-cost abundant carbon source) by first cross-linking it with glutaraldehyde, followed by deep freezing, carbonization and activation.…”
Section: Introductionmentioning
confidence: 99%